EXPERIMENTAL INVESTIGATION AND MODELING OF THE ELECTRIC FIELD DISTRIBUTION IN LIGHTNING PROTECTION SYSTEM - A., . Khechekhouche*; T., Guia; A., Hima (university of eloued جامعة الوادي, 2019)
The study presented in this paper highlights the electric field distribution of mutually horizontal and vertical lightning conductors with discontinuous earth. The conductors may be located in both higher or lower earth part. The electric field distribution was resolved in the case of lightning conductor placed between the high voltage rod and the discontinuity (interface). For this aim, we have used different results obtained by a numerical method for computation and an experimental model tested the efficacy of the finite elements methods (FEM). In some configurations the electric field distribution on the plan are less significant than definite by the electro-geometrical configuration. We suggested that effect to the grand field strength at the discontinuity part, which decrease the lightning conductor capture consequence. The results of this study are in harmony with the study relating to the electrical stress of such air gaps devoid of lightning
rtical
Keywords: Electrogeometrical model; Vertical lightning conductor; Discontinuous earth; Horizontal lightning conductor; the finite elements methods